Investigating Sense of Place and Geoethical Awareness among Educators at the 4th Summer School of Sitia UNESCO Global Geopark: A Quasi-Experimental Study - Koupatsiaris, Alexandros Aristotelis; Hara Drinia (Geosciences, 2024)
Anthropogenic global challenges and environmental pressures are increasingly significant. Developing pro-environmental behavior and geoethics is crucial for enhancing awareness, action capability, and respect for natural systems. UNESCO Global Geoparks (UGGps) play a vital role in conserving geological and biological diversity while aligning with the United Nations’ Sustainable Development Goals. This quasi-experimental study, conducted during the 4th Summer School of Environmental Education on Geotopes and Sustainability at the Sitia UGGp, uses a pre–post design and comprehensive questionnaire to explore changes in participants’ sense of place and geoethical awareness. Results indicate significant improvements in place attachment, place meaning, and geoethical awareness. These findings suggest that stronger emotional bonds and deeper personal meanings related to the Sitia UGGp correlate with increased geoethical awareness. This research highlights the role of psychological connections in influencing geoenvironmental ethics and underscores the importance of place-based emotional and cognitive bonds in fostering geoethical thinking. However, this study’s limited sample size and the specific geographic context of Sitia UGGp may limit the generalizability of the findings. Despite these limitations, this study provides insights into the interplay of emotions, meanings, and geoethics within the sustainability and resilience spectrum.